The impact of modified walking exercise incorporating intensity variations on increasing aerobic endurance - Fauzi Fauzi; Faidillah Kurniawan; Nur Cholis Majid; Noor Azuan Abu Osman (Jurnal Keolahragaan, 2023)
The aim of this study was to the effect of modified forms of exercise on increasing VO2Max in college students. In particular, This study focuses on assessing the effectiveness of interval training modifications, particularly in the form of walking exercises, in increasing VO2Max in college students. This study followed a quantitative approach, using an experimental design known as the one-group pre-test and post-test design. Cooper's test is used as a research instrument in this study. The study was undertaken with participants from the Department of Sports Development, Faculty of Sports Science, Universitas Negeri Yogyakarta, Indonesia. The findings of this study can be used as a reference for implementing a modified form of interval training, especially using walking patterns, to increase VO2Max in college students. Data analysis technique using Paired Sample t Test. The treatment group that underwent walking exercise experienced a significant increase in VO2Max, although the level of significance varied. In particular, the walking treatment group showed a significant increase with a significance value of 0.000.